Chemokine C-C motif ligand 2 suppressed the growth of human brain astrocytes under Ischemic/hypoxic conditions via regulating ERK1/2 pathway. (28th July 2020) - Yu, Min; Zheng, Ni; Jiang, Dudu; Wang, Lijing; Zhan, Qing; Zhao, Jiangmin
ABSTRACT: Primary Objective: Chemokine C-C motif ligand 2 (CCL2) plays a critical role in inflammation-related diseases in the central nervous system (CNS). However, the role of CCL2 in ischemic stroke remains unclear. Research Design: To investigate the role of CCL2 in ischemic stroke, we performed oxygen–glucose deprivation (OGD) on human brain astrocytes. Methods and Procedures: To assess cell proliferation, the CCK-8 assay was performed. Cell apoptosis was determined using flow cytometry. qRT-PCR and western blotting were utilized to measure gene expression. Main Outcomes and Results: Our results suggest that CCL2 and its receptor CCR2 are upregulated in OGD cells. Moreover, a CCL2 antibody significantly alleviated the ischemic/hypoxic-induced suppression of growth in human brain astrocytes. Human recombinant protein, CCL2, inhibited the growth of human brain astrocytes under normoxia conditions. These results demonstrate that CCL2 upregulation suppresses the recovery of human brain astrocytes under ischemic/hypoxic conditions. This effect was abolished by the ERK inhibitor PD98059. Therefore, CCL2/CCR2 activation may suppress the growth of human brain astrocytes through enhancing the activity of ERK1/2. Conclusions: Our results not only developed a deeper understanding of the role of CCL2 in human brain astrocytes but also provided novel insight into potential treatments for ischemic stroke.